Assessment of Expressive Written English Functioning Level of Class Th ree Pre-Lingually Deaf Learners in Kenya - Tobias Adera, Ogutu; Edwards Joash, Kochung; Peter Oracha, Adoyo; Peter Maina, Matu (2016)
Learners in different countries are currently being taught language at their functioning levels irrespective of their grades. Di strict English Evaluation Tests in Kenya have indicated that Class Thr ee prelingually deaf learners are being taught English above their fun ctioning level. However, the results did not show the learners’ functi oning level in expressive English. The purpose of the current study wa s to assess the learner’s functioning level in expressive written Engl ish. Theory of Syntax by Noam Chomsky which holds that learners acquir e language by mastering the vocabulary and the structure of the target language was adapted and used. The study employed evaluative and qual itative research designs. The population consisted of 337 Class Three prelingually deaf learners and 65 Class Three English teachers. Multi- Stage sampling technique was used to select 178 Class III prelingually deaf learners while purposive sampling technique was used to select 1 6 Class III English teachers of the deaf. Data was collected using a q uestionnaire and expressive written English test consisting of three s ub-tests. The instruments were verified for face and content validity by Class I-III English teachers of the deaf. The reliability of the in struments was established through test-retest using 34 (10%) learners and was determined using Pearson Product-moment correlation (r) at 0.7 0 or above, p<0.05. Data was analyzed using descriptive statistics and qualitative analysis. None (0.0%) of the 178 learners obtained the criterion pass mark of 50%. The learners’ functioning level in expres sive written English was found to be at Class I level at the beginning of the school year and were lagging behind the curriculum by three ac ademic years. It was found that the learners’ low functioning level in reading comprehension was due to lack of mastery of vocabulary, sente nce structue, cohesive ties and prior knowledge of the world around us . It was recommended that the teaching of English to Class III preling ually deaf learners in Kenya should begin at Class I level at the begi nning of the school year. The findings may be used by schools to start teaching Class Three prelingually deaf learners English at their func tioning level and by the Ministry of Education to inform policy.< /p>